Inovasi Pengembangan Sumber Daya Manusia untuk Meningkatan Kinerja Pendidik di Madrasah Ibtidaiyah Abdurrahman Bandung - Abdul Mutolib; Dicky Maryono (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research aims to explore innovations in human resource development aimed at enhancing the performance of educators at Madrasah Ibtidaiyah Abdurrahman in Bandung city. The research methodology employed is qualitative descriptive, utilizing data sources such as observations, interviews, documentation, and insightful conclusions drawn from interviews with the head of Madrasah Ibtidaiyah Abdurrahman in Bandung city. The findings of this study demonstrate a significant impact of human resource development innovations, utilizing current technology to improve educator performance. Training and development play a pivotal role in enhancing educator performance, supported by ongoing evaluation to mitigate performance decline.